Case report: Klinefelter syndrome may protect against the development of spinal and bulbar muscular atrophy - Akanuma, Haruna; Kadowaki, Suguru; Kanai, Kazuaki (Frontiers in Neurology, 2024)
Spinal and bulbar muscular atrophy (SBMA) is an X-linked recessive motor neuron disease caused by the expansion of cytosine-adenine-guanine (CAG) repeats in the androgen receptor (AR) gene. It is thought that the nuclear translocation of abnormal AR proteins following binding to testosterone triggers the onset of the disease. We report the case of a patient who had SBMA coincident with Klinefelter syndrome. He developed SBMA symptoms rapidly after receiving androgen replacement therapy for Klinefelter syndrome. No cases of coincident SBMA and Klinefelter syndrome have been reported, and if confirmed by further patients in future, that androgen hormones are strongly associated with the development and progression of SBMA in fact in humans.